THE EFFECT OF CAPITAL STRUCTURE, INSTITUTIONAL OWNERSHIP, AND COMPANY SIZE ON FINANCIAL PERFORMANCE IN PHARMACEUTICAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2024 - Indriyanti, Erlita Dwi; Devi, Sunitha; Musmini, Lucy Sri (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to determine the influence of capital structure, institutional ownership, and company size on financial performance. The type of research used is quantitative research using secondary data based on financial statements downloaded on the Indonesia Stock Exchange website and the company's website. The population in the study is 11 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2020-2024. Purposive sampling is the sampling method used in this study. The number of samples of 7 companies was collected using predetermined criteria. The data analysis techniques used were descriptive statistics, classical assumption analysis, multiple linear regression analysis, and hypothesis test. The phenomenon that occurred in pharmaceutical sub-sector companies was a decline in financial performance from 2021 to 2023 caused by the Covid-19 pandemic. The results of the study show that capital structure has a positive and significant effect on financial performance, institutional ownership does not have a significant effect on financial performance, and company size does not have a significant effect on financial performance.